Plan estratégico para el autoservicio “Ahorra Mas” de la ciudad de Catamayo provincia de Loja - Llivichuzca Pesantez, Zoila Marlene (2016)
In Ecuador the trading activity and mass distribution of products as well as food products in general also follows the route modernization designing marketing strategies, marketing, strategic planning, shopping channels, supply, distribution and sales that force development of complex and expensive structures to manage, store, sell and advertise a conglomeration of items that require very different for each steps. Such a variety of items (which is especially seen in supermarkets) led to the emergence of what is called management by product a mechanism by which the entire process of the supply chain is managed by different groups of people depending on the type article or service so you can have a group focused on the purchase, storage, distribution and sale of items requiring cold chain, one for items with manufacturer's warranty. It is for the reason cited above that the present research work stems from the need to improve the situation of the company "Save More" City Catamayenses is presented, as currently the company does not have a strategic orientation that allow it to results in their management, since its inception the company has not handled the basics of management concepts marketing alone which causes their results are not expected. Start with summary, which corresponds to a summary of the most important parts of the thesis. Introduction, with the importance of the subject under investigation, by 7 which a comprehensive understanding of all the work done will be highlighted. Literature review, it consists of citations containing theoretical contexts for strategic marketing plan, including: concepts and importance of the issues most commonly used in this work. Scientific, deductive, descriptive techniques such as direct observation, interview, and survey procedures used in the investigation that led collect the information necessary to determine facts and phenomena that occur in the environment: Materials and Methods in which the methods are detailed the company and to identify the key internal and external issues affecting the same, the same that have prevented normal solvency and development. The direct observation technique is used , the interview addressed to manager self-service and the survey of 180 self-service customers getting the sample size gives us a sample of 124 surveys to make customers and 12 employees same, then a SWOT analysis of the company, in which the internal factors such as the Strengths and Weaknesses and external factors are the opportunities and threats were determined is done, then the array of high-impact criteria and assessment is done with their respective percentages. In these considerations in results , the possibility of the present research work on " STRATEGIC PLAN FOR SELF- SERVICE " SAVE MORE " CITY CATAMAYO, province Loja, the same that was developed in the 8 raised Catamayenses city , with the overall objective to develop a strategic plan in order to improve the economic and competitive development of the Self, as well as the specific objectives is to develop the situational Self diagnostics, analysis of external factors in order to make the matrix external factors given as weighted result of 2.48 which means that threats are above the opportunities offered by the external environment, internal factors analysis to perform the matrix of internal factors as weighted result gives 2.52 which means that self and strengths that are almost equal to the same weaknesses; continues with the development of the SWOT matrix and the matrix of Al Impact to combine strategies obtained from the FA, FO, DO, DA, factors and synthesize each of the strategic objectives discussed in the Discussion of results of research, to finish with the conclusions, major research with their recommendations, the most important positions obtained during the application of analysis described all research work, so that the manager take corrective measures for your organization, Bibliography, is the part where you have to know the sources of information used in the development of this work and are last Annexes which were used as part of the investigation .